Estimação de equivalentes tarifários no comércio internacional de serviços - Pereira, João Ricardo de Loiola Macedo (2017)
Services account for more than 70% of total production in the world economy. However, international trade in this sector represents only 21% of total world trade. Literature suggests major impediments to further expansion of international trade in services are barriers imposed by countries. Based on Fontagné et al (2011), this study measures tariff equivalents for 14 types of services using a self-constructed database for the years of 2004, 2007 and 2011. Results suggest that developed countries such as Germany, United States, and Ireland present the lowest tariff equivalents while developing countries such as Laos, Togo, Rwanda, Malawi and Namibia charge the highest tariffs. Also, we find evidence that service barriers have been falling over time, for sectors and countries.